option A i.e. Three-fourths (four-thirds) x = negative 6 (four-thirds).
Explanation:
We have , The given expression as Three-fourths x = negative 6 , which can be written as
. Now in order to solve this equation in one step , we must notice that coefficient of x must be 1 but it's
, Let's make coefficient of x as 1 by multiplying both side of equations by 4/3:
![(3)/(4) (x) = -6](https://img.qammunity.org/2021/formulas/mathematics/middle-school/hs8zcl6s68hyr7kdqlu8bimvgcc1t03ppm.png)
⇒
![(3)/(4) (x) = -6](https://img.qammunity.org/2021/formulas/mathematics/middle-school/hs8zcl6s68hyr7kdqlu8bimvgcc1t03ppm.png)
⇒
![(3)/(4)((4)/(3) ) (x) = -6((4)/(3) )](https://img.qammunity.org/2021/formulas/mathematics/middle-school/5w9s3u988ujvt6qn388yo43bga7z0bbhug.png)
⇒
![x = -6((4)/(3) )](https://img.qammunity.org/2021/formulas/mathematics/middle-school/s3v562ooyqfj3y9ivo7ne83efuqdhvub9t.png)
⇒
![x = -2(4)](https://img.qammunity.org/2021/formulas/mathematics/middle-school/z0qu5hybez4c3redrv9fk56gnvz11er7kp.png)
⇒
![x = -8](https://img.qammunity.org/2021/formulas/mathematics/middle-school/q3eje5dh5aez97fnbrmj8y0zygnbjqy9kg.png)
Therefore, x= -8 & correct option to solve the equation Three-fourths x = negative 6 for x in one step is option A i.e. Three-fourths (four-thirds) x = negative 6 (four-thirds).